2012
DOI: 10.1007/82_2012_212
|View full text |Cite
|
Sign up to set email alerts
|

Production of Recombinant Antigens and Antibodies in Nicotiana benthamiana Using ‘Magnifection’ Technology: GMP-Compliant Facilities for Small- and Large-Scale Manufacturing

Abstract: This review describes the adaptation of the plant virus-based transient expression system, magnICON(®) for the at-scale manufacturing of pharmaceutical proteins. The system utilizes so-called "deconstructed" viral vectors that rely on Agrobacterium-mediated systemic delivery into the plant cells for recombinant protein production. The system is also suitable for production of hetero-oligomeric proteins like immunoglobulins. By taking advantage of well established R&D tools for optimizing the expression of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 71 publications
0
62
0
Order By: Relevance
“…Among them is the potential to scale upstream expression with considerably lower capital requirements compared to traditional cell culture processes. Plant viral replicons delivered within agrobacterial vectors have shown superior speed relative to transgenic plants and proven robust when scaled to industrially relevant settings [2, 46, 20, 23]. Conversely, if a large and continuous supply of a consistent AI is needed at low cost for industrial applications, the use of inducible promoters in transgenic plants grown in the field can offer advantages in obviating the production of very large volumes of agrobacterial inoculum and its application over large areas [5, 7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them is the potential to scale upstream expression with considerably lower capital requirements compared to traditional cell culture processes. Plant viral replicons delivered within agrobacterial vectors have shown superior speed relative to transgenic plants and proven robust when scaled to industrially relevant settings [2, 46, 20, 23]. Conversely, if a large and continuous supply of a consistent AI is needed at low cost for industrial applications, the use of inducible promoters in transgenic plants grown in the field can offer advantages in obviating the production of very large volumes of agrobacterial inoculum and its application over large areas [5, 7].…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis of BuChE, we used expression yields from several sources that evaluated various Agrobacterium -mediated expression systems, including Icon Genetics' magnICON expression technology (“magnifection”) [29, 34–36]. Magnifection should be familiar to most readers of this volume as it has been applied in R&D programs throughout the world and its features have been the topic of multiple original studies and reviews (see, e.g., Marillonnet et al [38]; Giritch et al [6]; Gleba and Giritch [39], Klimyuk et al [4], and Gleba et al [5]); therefore, the method is not described here in further detail. Likewise, the process of vacuum-assisted infiltration has been described in detail by Klimyuk et al [4], Gleba et al [5], and others and is not further explained here.…”
Section: Methodsmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40] Several previous studies have shown plant produced HA is effective in mouse and ferret models of influenza challenge, but always require at least two immunizations with adjuvant to stimulate HAI titers or protective immunity. 18,20,41 Disappointing results from a Phase I clinical trial reported only 5-10% seroconversion after 90 µg dosing with an HA vaccine, irrespective of adjuvant co-formulation, 42 or may require 2 doses of alum-adjuvanted vaccine for clinically significant immune protection.…”
Section: Discussionmentioning
confidence: 99%
“…Because preventive strategies ordinarily involve larger populations, an appropriate unit cost for a preventative antibody can be achieved at a sufficiently large production scale (7,8). The ability to scale up production without incurring excessive capital requirements or a change in production methods is a hallmark of production in plants (7).…”
Section: Production Of Mabs In Plants Rationale For Manufacturing Id mentioning
confidence: 99%
“…The technology appears to be the most rapid path from genes to full-length, assembled MAb, i.e., 14 days from gene delivery to purified MAb (10). The manufacturing technology can easily accommodate hundreds of grams per month for preclinical and clinical studies as well as commercial scale (7,8). Because antibody drug development has evolved into a highly iterative process where sequential modifications are introduced into candidate molecules and evaluated for changes in efficacy, the shortened time frame to multi-gram-level production may accelerate this process greatly.…”
Section: Transient Technologies For Plant-based Mab Productionmentioning
confidence: 99%